Stories from the Deep Earth How Scientists Figured Out What Drives Tectonic Plates and Mountain Building - Davies, Geoffrey F. (Cham : Springer International Publishing : Imprint: Springer, 2022)
Plate tectonics can drift continents and push up mountains, but what drives the plates? This is an insider's account of how we answered questions posed over two centuries ago, and completed geology's quest for a driving mechanism. Forging through confusing evidence, apparent contradictions and raging debates we arrived at not one but two mechanisms: sinking plates and rising plumes.
Chapter 1. Deep Earth and deep time, big ideas and big egos -- Chapter 2. The accidental geophysicist -- Chapter 3. A propitious time -- Chapter 4. Water, heat, time, mountains -- Chapter 5. Yielding rocks -- Chapter 6. Vagrant continents -- Chapter 7. Like nothing we've seen before -- Chapter 8. Novel ideas: plates and plumes -- Chapter 9. But what is the driving mechanism? -- Chapter 10. Chemistry and egos muscle in -- Chapter 11. Making it a science? -- Chapter 12. Some clarity: two convection modes, interacting -- Chapter 13. Earth's lessons: humility, power and science -- Chapter 14. Some chemical clarifying -- Chapter 15. Too noble? -- Chapter 16. Perspective; Imperfect but better than shouting.
Keywords: Geophysics; Geodynamics; Geochemistry; Geophysics; Geodynamics; Geochemistry